The effects of 5-aminolevulinic acid photodynamic therapy on the local immune response of women with cervical intraepithelial neoplasia grade 2 - Wu, Anyue; Niu, Jing; Hong, Zubei; Gu, Liying; Huang, Yuli; Qiu, Lihua (Frontiers in Immunology, 2023)
Objective: To evaluate and elucidate the effects and mechanism of photodynamic therapy (PDT) on the immune response of women with cervical high-grade squamous intraepithelial lesions (HSILs). Methods: Immunofluorescence staining was used to compare immune infiltration before and after PDT in 23 patients with cervical HSILs. The infiltration of immune cells into the cervical tissues of patients with different outcomes was also compared at the 6-month follow-up period. Immune cell counts in samples collected before and after treatment were compared. Results: We found an increased number of CD8+ T cell infiltration, an increased proportion of CD8+ T cells expressing Granzyme B (GrB), Chemokine receptor 3 (CXCR3), and CD8+ tissue-resident memory T (TRM) cells, and a decreased proportion of CD8+ T cells expressing PD-1 in patients with cervical HSIL compared to that before PDT. Moreover, at the 6-month follow-up, there was higher infiltration of CD8+ T and CD8+ TRM cells, higher expression of GrB and CXCR3, and lower expression of PD-1 on CD8+ T cells in the HPV and cervical HSIL clearance groups than in the persistent HPV infection and cervical HSIL regression groups. However, no significant difference was observed in the number of CD8+ TSCM following PDT. Conclusions: PDT activates immune responses mediated by CD8+ T cells. The degree of the immune response is correlated with the prognosis of cervical HSIL.